2021
DOI: 10.3390/molecules26102961
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Anticancer Screening for Repurposed Pyrazolo[3,4-d]pyrimidine Derivatives on Four Mammalian Cancer Cell Lines

Abstract: The present study reports the synthesis of new purine bioisosteres comprising a pyrazolo[3,4-d]pyrimidine scaffold linked to mono-, di-, and trimethoxy benzylidene moieties through hydrazine linkages. First, in silico docking experiments of the synthesized compounds against Bax, Bcl-2, Caspase-3, Ki67, p21, and p53 were performed in a trial to rationalize the observed cytotoxic activity for the tested compounds. The anticancer activity of these compounds was evaluated in vitro against Caco-2, A549, HT1080, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Ki-67 is a nuclear protein that is associated with cellular proliferation. It was reported that chemotherapeutic agents caused decrease in its expression 58 .…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 is a nuclear protein that is associated with cellular proliferation. It was reported that chemotherapeutic agents caused decrease in its expression 58 .…”
Section: Discussionmentioning
confidence: 99%
“…It is widely reported that several TK inhibitors exhibit anti-liver fibrotic activity [ 91 , 92 , 93 , 94 ]. Hence, we examined for the first time the hepatoprotective effect of three celecoxib structurally related derivatives that were reported as kinase inhibitors having antineoplastic activity [ 21 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some pyrazole-based compounds have been reported to have antifibrotic potentials [ 17 , 18 , 19 ]. Among these, some new pyrazolo[3,4-d]pyrimidines were reported to suppress COX-2 expression at low concentrations [ 20 ], while others possessed antineoplastic activity and were reported as kinase inhibitors [ 21 ]. Consequently, such traits of new pyrazole-based compounds would serve as potential therapeutic candidates targeting HSCs to ameliorate liver fibrosis without being toxic to normal cells.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of p53 protein function is correlated with the growth of liver cancer and poor prognosis (63). Ki67 has a remarkable value in providing evidence of prognostic value caused by tumor growth and proliferation (64). To investigate the correlation between gut microbiota and environmental factors, we evaluated AFP, p53, Ki67, CK19, Th/Ts, C3, and IgG.…”
Section: Discussionmentioning
confidence: 99%